Treatment-dependent changes in cytokine profile of capillary and venous blood in patients with psoriasis - S. V. Sennikova; A. P. Toptygina; A. A. Kolobov; A. S. Simbirtsev (Медицинская иммунология)
Psoriasis is a chronic autoimmune skin disease with affected T-cell immunity. The interleukin IL-23/IL-17/IL-22 cytokine axis is a key to immunopathogenesis of psoriasis. Certain role of the IL-36 subfamily is shown in regulation of skin inflammation. Topically applied preparations are used to treat psoriasis. Our aim was to evaluate the treatment-related changes in the cytokine profile of venous and capillary blood collected close to the foci of psoriatic inflammation. Forty patients with psoriasis (mean age, 43.7 years), were examined. Group 1a (20 people) received local treatment with Mometasone, Group 1b (20 people) received topical gel containing an IL-36 receptor antagonist. Twenty healthy people (mean age, 46.6 years) comprised the control group 2. 200-μL aliquots of capillary blood were collected in a microvette with EDTA from the patients’ finger near to the lesion area. Venous blood (3 mL) was taken from the cubital vein to a vacuum tube with EDTA. The concentration of 15 cytokines in blood plasma was tested by the multiplex method (MagPix, BioRad, USA). Clinical effectiveness of therapy was assessed using the PASI and DLQI indexes. Upon completion of treatment (day 14), the PASI and DLQI indices were significantly decreased in both groups. On the 28th day, the PASI index in Group 1a returned to its original level, in group 1b it remained permanently reduced. Before treatment, the levels of all cytokines, except of IL-10, were significantly increased in capillary blood samples of patients with psoriasis compared to Group 2, and the levels of five cytokines were increased in the venous blood. In group 1a, the levels of IL-1, IL-4, IL-6, IL-21, IL-22, IL-23, IL-25, IL-33 were significantly decreased in capillary blood after 14 days, and only IL-17F, IL-21, IL-33 and TNF showed a decrease in the venous blood specimens. On the day +28, the concentrations of almost all cytokines returned to their original level. In Group 1b, on the 14th day, the levels of IFNγ, IL-1, IL-4, IL-17F, IL-21, IL-22, IL-23, IL-25, IL-33 were significantly decreased in capillary blood compared to altered IFNγ, IL-21, IL-22, IL-23, IL-33 in venous blood. On the 28th day, their concentration continued to decrease, or the level of these cytokines remained reduced, along with significant decrease of IL-6 in venous samples. Thus, the method for determining cytokine profile in capillary blood from the area of psoriatic lesions may be used for tracing the effects of therapy in psoriatic patients.